Evaluation of the portio vaginalis of the cervix by B-mode and colour Doppler ultrasound in Simmental cattle - Risvanli, Ali; Safak, Tarik; Yilmaz, Oznur; Yuksel, Burak; Kilinc, Mehmet Akif; Seker, Ibrahim (Veterinarni A Farmaceuticka Univerzita Brno, 2022)
This study was aimed to reveal the relationship between the B-mode and colour Doppler ultrasonography features of the portio vaginalis of the cervix in Simmental cattle with different physiological and pathological conditions of genital organs. For this purpose, 90 cattle were used in the study. The length, width and circumference of the portio vaginalis of the cervix were measured ultrasonographically using a 5 MHz linear probe. In addition, the portio vaginalis of the cervix was ultrasonographically evaluated in terms of echogenicity, cystic formations, calcification and integrity of its borders. Regarding the colour Doppler ultrasonography, measurements of the vascular distribution category, vascular density and the vascular morphological appearance were made. In this study, it was found that the rate of irregularity of the border of the portio vaginalis in B-mode ultrasonography according to the pregnancy status was 10.9% in non-pregnant cows, while this was not observed in pregnant cows (0.0%). According to the metritis status, it was observed that the rate of regularity of the border of the portio vaginalis was higher in animals with metritis (45.5%) in B-mode ultrasonography. As a result, it was concluded that there were significant changes in the B-mode and colour Doppler ultrasonography characteristics of the portio vaginalis of the cervix in different physiological and pathological conditions in cattle, and that hypotheses can be developed regarding the fertility of the animals by evaluating these characteristics.
Keywords: Calcification; echogenicity; cystic formation